(untitled) (Research, Society and Development, 2020)
The teaching practice is a complex task which requires planning, zeal for the profession, ethics and commitment. This article aims to report the experience of students at masters level of the Graduate Program in Health and Community of the Federal University of Piauí as teachers in the discipline of Nursing and health care praxis for nurses of the Multiprofessional Residency in Family Health / Primary Care , in the year of 2018, in a Federal University of the coast of Piauí. It focuses also on the experience of students at masters level with the discipline Didactics offered by the Graduate Program in Health and Community. The methodology applied in this study is a qualitative, descriptive study of the type experience report. During the classes taught by the teachers were held group dynamics, the presentation of the course and the evaluation methods, hopscotch, discussion of scientific article, expository presentation of lessons through slides, questioning the content through text, presentation of the ideas box, evaluation of the discipline. The pieces of information from the experience report were collected through the teachers’ classes and field diaries. The results of this study showed that the teaching practice requires the search for new teaching methodologies that provide a critical eye at the reality, transforming it. It is understood that, through this experience, the attitude assumed by the teachers was to mediate the learning process, since they instigated the student to "learn to learn", which contributed considerably to the production of knowledge by students and for the teachers.